Games without Frontiers: A Framework for Analyzing Digital Game Cultures Comparatively - Elmezeny, Ahmed (2018)
Currently in game studies there is a gap in frameworks for comparatively researching game cultures. This is a serious shortcoming as it ignores the transcultural and transnational aspects of games, play and their cultures. Based on Hepp’s (2009) transcultural framework, and Du Gay, Hall, Janes, Mackay and Negus’s (1997) circuit of culture, this article proposes a structure to comparatively analyze game cultures. This procedural method comprises several steps determining specific contexts of game culture and their categories for comparison. Each step is illustrated with a case example. Finally, we recommend placing game cultures on a transnational spectrum, which helps in suggesting that many digital games express both local and international characteristics.